Black Men's Experiences With Health care: Individuals' Accounts of Challenges, Suggestions for Change, and the Potential Utility of Virtual Agent Technology to Assist Black Men With Health Management. (August 2021) - Kramer, Justin; Yinusa-Nyahkoon, Leanne; Olafsson, Stefan; Penti, Brian; Woodhams, Elisabeth; Bickmore, Timothy; Jack, Brian W
Black men have the highest age-adjusted death rate of any major race-gender group in America. Understanding their perceived barriers to accessing health care may benefit future interventions working to increase Black men's health care engagement. Data collected from focus groups of Black men( N = 67), key informant interviews( N = 12), and interviews( N = 5) with participants who pilot tested an online health education system (called "Gabe") were analyzed to explore their health care experiences and how computer-based health programs might better assist Black men. Concerns pertaining to health care systems' failure to recognize the diversity among Black men, and physicians' lack of sociocultural awareness about the challenges they regularly face, were most salient. Building trust with providers was cited as being central to engagement, with Gabe users perceiving the system to be both trustworthy and accessible. Participants reported an openness to technology assisting with health management and provided suggestions of how online systems can meet the needs of Black men.